Efektivita práce učitele v inkluzivním vzdělávání: sebehodnoticí nástroj pro studující pedagogických odborů - Vaďurová, Helena (Masaryk University Press, 2022)
Title in English: Effectiveness of the teacher's work in inclusive education: A self-assessment tool for students of pedagogic fileds For teachers, to be able to fulfill the role "of carrier of change", he or she must be identified with the idea of education for all, accept responsibility for the education of all his or her students, and be able to recognize and solve any form of exclusion and unequal. At the same time, it turns out that a fundamental factor forming the teachers' actions in the inclusive classroom is their inner confidence in their own ability to manage individual aspects of educational activities. The tool makes it possible to view the teacher's work from a distance, learn to reflect on it and create a personal and professional development plan.